2007
DOI: 10.7150/ijms.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Strength training improves muscle quality and insulin sensitivity in Hispanic older adults with type 2 diabetes

Abstract: Hispanics are at increased risk of morbidity and mortality due to their high prevalence of diabetes and poor glycemic control. Strength training is the most effective lifestyle intervention to increase muscle mass but limited data is available in older adults with diabetes. We determined the influence of strength training on muscle quality (strength per unit of muscle mass), skeletal muscle fiber hypertrophy, and metabolic control including insulin resistance (Homeostasis Model Assessment –HOMA-IR), C-Reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
265
3
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(295 citation statements)
references
References 48 publications
15
265
3
12
Order By: Relevance
“…Similar results were observed by Brooks et al (2007), who observed a reduction of 1.2 % in the HbA1c levels (P < 0.05) after 16 weeks of resistance training performed three times per week consisting of three sets of eight repetitions at an intensity ranging from 60 to 80 % of 1 RM. In all of these studies, no significant alteration in glycemic control was observed in the control group that did not perform any exercise intervention.…”
Section: The Effects Of Resistance Trainingsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results were observed by Brooks et al (2007), who observed a reduction of 1.2 % in the HbA1c levels (P < 0.05) after 16 weeks of resistance training performed three times per week consisting of three sets of eight repetitions at an intensity ranging from 60 to 80 % of 1 RM. In all of these studies, no significant alteration in glycemic control was observed in the control group that did not perform any exercise intervention.…”
Section: The Effects Of Resistance Trainingsupporting
confidence: 87%
“…In addition to its important effect on glycemic control, resistance training is a very important intervention because it counteracts the exacerbated loss of muscle strength and functional capacity observed in elderly patients (Castaneda et al 2002;Dunstan et al 2002;Brooks et al 2007;Ibañez et al 2008;Geirsdottir et al 2012). For example, in study of Brandon et al (2003), 24 weeks of resistance training performed at moderate intensity induced increases in muscle strength and mobility in elderly with type 2 diabetes.…”
Section: Functional Capacity In Elderly Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a significant difference was observed in the plasma level of adiponectin in the experimental group between the pre-test and post-test stages. The increase in the plasma level of adiponectin as a result of 12 weeks of aquarobics exercises was most likely a preventive factor for diseases related to adiponectin (32,36). In this research, the increase in the level of adiponectin after adjusting to the aquarobics exercises was similar to the results of a number of previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…Resistance training in particular has been seen to improve both muscle strength and 20 mass as well as insulin sensitivity (Brooks et al, 2007;Cauza et al, 2005;Dunstan et 21 al., 2002;Holten et al, 2004;LeBrasseur et al, 2011;Mann et al, 2014). For these 22 reasons, it may be desirable that type 2 diabetes patients would begin an appropriate 23 exercise training program as soon as possible after diagnosis to prevent, or at least 24 limit, the decline in neuromuscular function.…”
Section: Introductionmentioning
confidence: 99%